Substance Abuse Among Medical Students – A Survey in a Medical College in Nepal - Roy, Roshan Kumar; Roy, Deepak Kumar; Goit, Rajeh Kumar (Journal of Nepalgunj Medical College, 2018)
Introduction: Substance use among medical students could impact on the conduct, safety and efficiency of future doctors. Despite serious medico legal, ethical and political ramifications, there is paucity of published article on the subject, especially from Nepal. Objective: We aimed to explore the patterns of substance abuse among a sample of Medical students from Nepalgunj Medical College. Materials and Methods: A cross-sectional survey of medical students from Nepalgunj Medical College was done using a brief questionnaire schedule to identify current and lifetime use of tobacco, alcohol, cannabis and abuse of other drugs. An operational definition of substance abuse was made, 28 % of students fell within that criterion. Results: Male substance abusers 81% exceeded female abusers 19%. Substances most commonly abused were alcohol 60%, minor tranquilizers 48%, and tobacco 35%, and only 11% abused cannabis. While most students were multidrug users, there was a low frequency of daily drug use. A general lifetime (occasional use) prevalence of substance use of 56% was found. Drugs consumed on a daily basis were alcohol 2% and tobacco 6%. The prevalence of drug use was highest among the fourth and final year students. Conclusion: The majority of students were occasional abusers; there was no evidence of physical dependence. This study provides a snapshot of the problem of substance use among medical students of Nepal. Further research is needed to study nationwide patterns of substance use among medical students, and to identify important determinants and reinforce preventive measures. Strategies need to be developed for supporting students with a substance use problem.